Relative impact of radiographic osteoarthritis and pain on quadriceps strength, proprioception, static postural sway and lower limb function. Issue 7 (24th November 2005) - Hall, M C; Mockett, S P; Doherty, M
Abstract : Objective: To investigate the relative impact of radiographic osteoarthritis (ROA) and current knee pain on lower limb physical function, quadriceps strength, knee joint proprioception, and postural sway. Methods: Using a 2×2 factorial design, 142 community derived subjects aged over 45 were divided into four subgroups based on the presence or absence of ROA (Kellgren & Lawrence >grade 2) and knee pain (as assessed by NHANES questions and a 100 mm visual analogue scale). Maximum isometric contraction of the quadriceps, knee joint proprioceptive acuity, static postural sway, and WOMAC index (both whole and function subscale) were assessed in all subjects. Results: Compared with normal subjects, reported disability was greater for all other subgroups (p<0.01). Subjects with both ROA and knee pain reported the greatest disability, and those with knee pain only had greater disability than those with ROA only. Quadriceps weakness was observed in all groups compared with normal subjects (p<0.01), though they were no significant intergroup differences. Subjects with knee pain had a greater sway area than those without (p<0.05) but the presence of ROA was not associated with increased postural sway. No differences in proprioceptive acuity were observed between groups. Conclusions: The presence of knee pain has a negative association with quadriceps strength, postural sway, and disability compared with ROA. However, the presence of pain-free ROA has a significant negative influence on relative quadriceps strength and reported disability.